Faktor-Faktor Yang Mempengaruhi Income Smoothing Pada Perusahaan Manufaktur Periode 2014-2016 - Lukman Suryadi, William Sanjaya, (Jurnal Ekonomi, 2018)
The purpose of this empirical research is to examine the effect of firm size, financial leverage, profitability, and cash holding against income smoothing in the manufacturing companies listed on the Indonesia Stock Exchange from 2014-2016. This research uses 63 manufacturing companies that were selected using purposive sampling method for a total of 189 data in three years.In this study, the hypotheses test is performed using the logistic regression model.The results showed that profitability, cash holding and firm size has no effect on income smoothing. Financial Leverage has a negative influence on income smoothing.